The Influence of Storytelling to Improve Students’ Speaking Skill - Khairunnisa, Fitri; Anggraeni, Anita (PROJECT (Professional Journal of English Education), 2025)
This study is aimed to discover whether storytelling can improve students’ speaking skill or not of ninth-grade students in Bandung. The research method used is the experimental method, while the research instrument used is one group pre-test and post-test. The sample of this research is the students of class 9, with a total of 25 students. Based on data analysis results using SPSS, the result of the pre-test is 56.88. Meanwhile, the result of the post-test is 77.76. Two hypotheses guided the researcher: the Null hypothesis (H0:) storytelling can not improve students’ speaking skills, and the alternative hypothesis: storytelling can improve students’ speaking skills. In summary, the Null hypothesis is rejected which conclude that storytelling can improve students’ speaking skill.